2017
DOI: 10.1016/j.jclepro.2017.07.136
|View full text |Cite
|
Sign up to set email alerts
|

Waterless purification using oil palm biomass-derived bioadsorbent improved the quality of biodiesel from waste cooking oil

Abstract: The utilization of adsorbents produced from biomass for tertiary treatment of industrial wastes has gained much interest compared to the conventional methods such as flocculation and coagulation. In the present study, a bioadsorbent produced from pressed-shredded oil palm empty fruit bunch was used to remove impurities from crude biodiesel derived from waste cooking oil. The purification process was performed using 1 to 5 wt% bioadsorbent loadings under continuous stirring at 500 rpm for 1 h. After purificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The activated carbon was successfully applied for biologically treated POME by reducing around 23% of COD and 88% of suspended solid. In a study by Ahmad Farid et al, activated carbon‐derived OPEFB was produced via a two‐step process that began with carbonization and was followed by KOH activation under a continuous flow of N 2 at 700 °C. As a result, the highest specific surface area of 694.2 m 2 g −1 was obtained.…”
Section: Emerging Technologies For Renewable Materials Production Fromentioning
confidence: 99%
“…The activated carbon was successfully applied for biologically treated POME by reducing around 23% of COD and 88% of suspended solid. In a study by Ahmad Farid et al, activated carbon‐derived OPEFB was produced via a two‐step process that began with carbonization and was followed by KOH activation under a continuous flow of N 2 at 700 °C. As a result, the highest specific surface area of 694.2 m 2 g −1 was obtained.…”
Section: Emerging Technologies For Renewable Materials Production Fromentioning
confidence: 99%
“…On the other hand, bubble-washing is highly recommended and can be easily implemented to the existing technology by aeration from the bottom of washing vessel. 22 Abbaszadeh et al 21 investigated the influence of water type (tapped, distilled, and water with 3 % phosphoric acid), water to biodiesel ratio (0.5, 1, 1.5 v/v), and temperatures (30,45, and 60 °C) on biodiesel purification. They applied bubble-washing technique.…”
Section: Wet Washingmentioning
confidence: 99%
“…In order to reduce the costs, as well as to be more environmentally friendly, natural adsorbents, like agro-industrial waste and/ or waste/by-products from food industry, can be used. [27][28][29][30][31] Despite all the good results, the main disadvantages of dry washing processes for crude biodiesel purification are related to the commercial adsorbents price and their reuse and disposal. 29 On the other hand, the great advantage is the use of natural adsorbents (waste/by-products from food industry and/or agro-industrial waste), while good results have already been achieved as reported previously.…”
Section: Dry Washingmentioning
confidence: 99%
“…Several researchers have shown increased interest in the use of activated carbons in the dry washing method of biodiesel purification. Farid et al [49] worked to improve the biodiesel quality produced from waste cooking oil using palm-derived biosorbent. They produced biosorbent by a two-step process, beginning with carbonization in a furnace and then by activation (700 C for 2 h) and neutralization (0.1 M HCl).…”
Section: Activated Carbonsmentioning
confidence: 99%